(untitled) (Fiep Bulletin - online, 2015)
A Physical Education professional’s job is to assure a healthy life to others, but most of the times, they don’t take care of their own health, fitting under the saying “do what I say, don’t do what I do”. One of their working areas is to evaluate people’s conditions, using it to diagnosis their body condition and to help to understand if their goals are being achieved with the exercises. One of the problems during an evaluation is the tension in between the evaluator and the person that’s being evaluated, that could alter heart rates (HR), do to sympathetic nervous system (SNS) actions and the catecholamine. The SNS is responsible to increase HR, myocardium’s contraction strength and the catecholamine liberation, dominating in physical and emotional stress situations. Powers(2000), relates the SNS actions to Cannon’s theory where this all happens to prepare the person to fight or run from a extreme dangerous situation. Objective: Verify the HR responses in between evaluators when evaluating the same person. Methods: It was a descriptive research with 4 men and 3 women, averaging age of 25,5+/-7,1 e 29,0+/-8,7 .Results: It was verified with anthropometric actions the average HR of 91,89+/-6,86 e 89,45+/-6,18, skin fold de 94,36+/-2,41 e 89,72+/-2,10, bone’s diameter 94,52+/-7,66, and 90,58+/-6,01 for flexibility neuromuscular components, Wells bench 96,78 +/-7,03 e 97,67+/-68,6 Flexitest, 106,30+/-11,21 and 105,46+/-8,60, for indirect strength for superiors muscles 103,62+/-11,16 e 102,75+/-7,92 , Abdominal 1’ 97,80+/-11,34 and 105,80+/-9,34 Dynamometrical 97,50+/-13,85 and 96,44+/-10,63 respectively. Conclusion: According to the literature, females are considered to have a higher HR than males, and this research showed that it could varies depending on the area that’s evaluated and a difference on the technique when it’s requested strength from both genders.